Role of Nutrition in Coronary Bypass Surgery - Benalikhoudja, H.; Abdelbaki, M.; Boudiaf, E. (Clinical Medicine And Health Research Journal, 2023)
Preventive nutrition in cardiology has a bright future ahead of it, as there is abundant data to justify its importance in secondary prevention. Practitioners must appropriate these simple data to meet patients' expectations. Our work consisted in showing the interest of nutrition and moderate physical activity in the secondary prevention of risk factors of coronary disease after coronary bypass surgery. Our study included 20 patients, all of whom were operated on according to the same therapeutic protocol. We will also review the effects of several nutrients, foods, and dietary patterns. The results found are correlated with those found in the literature. The Mediterranean diet has accumulated the most evidence. The challenge is to change patients' habits, but this depends in part on the conviction and motivation of doctors.